The emerging relationship between interstitial fluid-cerebrospinal fluid exchange, amyloid β and sleep - Boespflug, Erin L. (Biol Psychiatry, 2017)
Amyloid β (Aβ) plaques are a key histopathological hallmark of Alzheimer’s disease (AD) and soluble Aβ species are believed to play an important role in the clinical development of this disease. Emerging biomarker data demonstrates that Aβ plaque deposition begins decades before the onset of clinical symptoms, suggesting that understanding the biological determinants of the earliest steps in the development of AD pathology may provide key opportunities for AD treatment and prevention. Although a clinical association between sleep disruption and AD has long been appreciated, emerging clinical studies and insights from the basic neurosciences has shed important new light on how sleep and Aβ homeostasis may be connected in the setting of AD. Aβ, like many interstitial solutes, is cleared in part through the exchange of brain interstitial fluid and cerebrospinal fluid (CSF) along a brain-wide network of perivascular pathways recently termed the ‘glymphatic’ system. Glymphatic function is primarily a feature of the sleeping, rather than the waking brain, and is slowed in the aging and post-traumatic brain. These changes may underlie the diurnal fluctuations in interstitial and CSF Aβ levels observed in both the rodent and human. These and other emerging studies suggest that age-related sleep disruption may be one key factor rendering the aging brain vulnerable to Aβ deposition and the development of AD. If true, sleep may represent a key modifiable risk factor or therapeutic target in the pre-clinical phases of AD.